Improving the User Interface and Experience of a Student PortalThrough the Eight Golden Rules - Arwin Datumaya Wahyudi Sumari; Fatiha Eros Perdana; Dwi Nugraheny; Sandra Lovrencic (Universitas Bumigora, 2025)
One of the crucial web-based academic service facilities in higher education is the Student Portal. Based on a survey of student users, the existing Student Portal at the Institut Teknologi Dirgantara Adisutjipto (Design A) is visually unappealing. It therefore requires improvement in terms of User Interface (UI) design. The purpose of this study is to enhance the UI and UX of the Student Portal. The method used involved applying the Eight Golden Rules method and the Maze tool to design the UI. The resulting new design (Design B) and the current one (Design A) were tested using A/B testing. This study involved a sample of 41 student users from the Informatics Study Program, as they were considered familiar with UI/UX, along with four staff users selected to represent the overall population of Student Portal users. The instrument that is used to evaluate both designs is the System Usability Scale (SUS). The test results show that Design A received an average score of 55.0, which falls into the ”OK” category with a grade of D. In contrast, Design B, which incorporates the Eight Golden Rules method, achieved an average score of 75.0, placing it in the ”GOOD” category with a grade of B. In conclusion, the application of the Eight Golden Rules method led to a 36.4% improvement inthe UI and UX of the Student Portal.